Pengaruh Profesionalisme Kerja, Stres Kerja dan Psikologis Karyawan terhadap Kinerja Karyawan pada PT BFI Cabang Mamuju - Halim, Agus; Ramadhan, Adam; Yeni, Hari; Naska N, Naska N (Journal of Management Branding, 2025)
PT BFI Finance is one of the companies engaged in financing. This company is an independent company that has branches in various regions, one of which is in Mamuju which was established on October 11, 2010. This research was conducted with the aim of knowing the effect of work professionalism, work stress and employee psychology on employee performance at PT BFI Finance Mamuju Branch. This research uses quantitative methods, with sample withdrawal using probability sampling techniques with 30 respondents. Data collection was carried out by observation, interviews, and distributing questionnaires directly to respondents. Testing the quality of research instruments using validity tests, and reliability tests. The analytical tool used is multiple linear regression analysis, then hypothesis testing using partial test (t statistical test), and simultaneous test (F statistical test). The research results obtained (1) work professionalism has a significant partial effect on employee performance. (2) job stress has a partial and significant effect on employee performance. (3) employee psychology has a partial and significant effect on employee performance. (4) Work professionalism, work stress and employee psychology simultaneously have a significant and significant effect on employee performance